Cervical Spine Minimally Invasive and Open Surgery - Menchetti, Pier Paolo Maria (Springer International Publishing : Imprint: Springer, 2016)
This book addresses conventional and minimally invasive surgery of the cervical spine  to cater for both experts and young surgeons with less experience in this field of surgery. It is written by a group of highly trained specialists from all over the world, who present the requirements for the most advanced surgical techniques on the cervical spine. Most of the chapters concern the osteodiscoarthrosic pathology, the main condition responsible for chronic cervical and/or radicular pain. Step by step presentations of the most advanced MISS (endoscopy) and standard procedures such as ACDF (anterior cervical decompression and fusion), using cages or autologous bone, posterior approach to axis instability, minimally invasive stabilization systems, and cervical disc arthroplasty are examined for the treatment of the osteodiscoarthrosis. Looking towards the future, this book also includes chapters about the role of materials in cervical spine fusion and biomechanical engineering evaluation in cervical tribology. Considering the growing incidence of cervical spine discoarthrosis, the authors aim to provide an expert overview of cervical spine surgery to assist the medical community with treating this increasingly common pathology.